Practical implementation of the Endocarditis Team in 'functional' reference centres: the Italian hospital network experience and recommendations of the Italian Society of Echocardiography and Cardiovascular Imaging. Issue 7 (July 2019) - Cecchi, Enrico; Chirillo, Fabio; Moreo, Antonella; Graziosi, Maddalena; De Michele, Lucrezia; Faggiano, Pompilio; Mattioli, Roberto; Polizzi, Vincenzo; Labanti, Graziana; Benedetto, Frank A.; Colonna, Paolo
Abstract : N/A: The 2015 European Society of Cardiology (ESC) guidelines for the management of infective endocarditis recommend the use of a multidisciplinary team in the care of patients with infective endocarditis. A standardized collaborative approach should be implemented in centres with immediate access to different imaging techniques, cardiac surgery and health professionals from several specialties. This position paper has been produced by the Task Force for Management of Infective Endocarditis of Italian Society of Echocardiography and Cardiovascular Imaging (SIECVI) with the aim of providing recommendations for the implementation of the Endocarditis Team within the Italian hospital network. On the basis of the Italian hospital network with many cardiology facilities encompassing a total of 405 intensive cardiac care units (ICCUs) across the country, 224 (3.68 per million inhabitants) of which have on-site 24-h PCI capability, but with relatively few centres equipped with cardiac surgery and nuclear medicine, in the present article, the SIECVI Task Force for Management of Infective Endocarditis develops the idea of a network where 'functional' reference centres act as a link with the periphery and with 'structural' reference centres. A number of minimum characteristics are provided for these 'functional' reference centres. Outcome and cost analysis of implementing an Endocarditis Team with functional referral is expected to be derived from ongoing Italian and European registries.